Sociodemographic Determinants of Knowledge towards Tuberculosis Transmission among Women of 15–49 Years of Age in India - Baikunth Kumar Yadav; Pranveer Singh; Bijaya Kumar Padhi (Advances in Public Health)
Background. India is one of the countries in the world most heavily impacted by tuberculosis (TB). In 2015, TB was a leading cause of death, killing 1.4 million people worldwide. The aim of the study was to assess the knowledge and associated factors regarding the transmission of TB among women in India. Method. We used publicly available datasets collected as part of the NFHS during 2015–16 in India. Data related to sociodemographic factors and knowledge about the transmission of TB among women (N = 699,686) were extracted using STATA. Multiple logistic regression analyses were used to determine factors associated with the knowledge of TB transmission among women. Results. Among 699,686 women, 88.36% knew about TB, 59.81% recognized that tuberculosis spreads by air through coughing or sneezing, and 78.55% understood that tuberculosis is a curable disease indicating correct knowledge about TB. 70.74% of the women were from rural areas with 59.29% having a secondary or higher level of education and 40.41% living in poverty. Multivariable analysis indicated that the probability of having good knowledge of TB was consistently significant among women with higher education [aOR: 2.502; 95% CI: 2.454–2.551]; women living in rich households (highest wealth quintile) [aOR: 1.590; 95% CI: 1.556–1.625]; and women residing in urban areas [aOR: 1.191; 95% CI: 1.166–1.215] than their rural counterparts. Conclusion. The findings of this study showed that women in India have moderately good knowledge and a correct attitude towards tuberculosis. However, the level of information varies with the various sociodemographic factors such as age group, place of residence, education, wealth index, religion, and caste/tribe bearing a positive causal relationship between the knowledge and TB transmission and hence the resulting attitude.